Smartphone-Based Biosensor Devices for Healthcare: Technologies, Trends, and Adoption by End-Users - Madrid, Rossana Elena (2022)
Smart biosensors are becoming an important support for modern healthcare, even more so in the current context. Numerous smartphone-based biosensor developments were published in recent years, some highly effective and sensitive. However, when patents and patent applications related to smart biosensors for healthcare applications are analyzed, it is surprising to note that, after significant growth in the first half of the decade, the number of applications filed has decreased considerably in recent years. There can be many causes of this effect. In this review, we present the state of the art of different types of smartphone-based biosensors, considering their stages of development. In the second part, a critical analysis of the possible reasons why many technologies do not reach the market is presented. Both technical and end-user adoption limitations were addressed. It was observed that smart biosensors on the commercial stage are still scarce despite the great evolution that these technologies have experienced, which shows the need to strengthen the stages of transfer, application, and adoption of technologies by end-users.